STRATEGI GURU UMUM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI SISWA TUNARUNGU DI SDLB NEGERI SAMBAS PADA MASA PANDEMI COVID-19TAHUN PELAJARAN 2021-2022 - Lulu Noflya; Nuraini Nuraini; Astaman Astaman (CV. ADIBA ASIHA AMIRA, 2025)
This thesis discusses general teacher strategies in learning Islamic religious education for deaf students at SDLB Negeri Sambas. The research has three objectives, namely: First, to find out the various strategies of general teachers in teaching Islam for Deaf Students at the Sambas State Elementary School during the Covid-19 Pandemic for the 2021-2022 Academic Year. Second, knowing the application of various general teacher strategies in teaching Islam for Deaf Students at the Sambas State Elementary School during the Covid-19 Pandemic. Third, find out the obstacles in learning Islam for deaf students at the Sambas State Elementary School during the Covid-19 pandemic. This research is a descriptive, qualitative study which aims to find out what strategies are used by general teachers in learning Islamic religious education for deaf students at SDLB Negeri Sambas. The subjects of this research were general teachers at SDLB Negeri Sambas. Data collection tool techniques are: observation, interviews, documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, verification and drawing conclusions. Then the data validity checking technique used is triangulation and member check. The results of this research are: First, general teacher strategies in learning Islamic religious education for deaf students, namely expository strategies, individual strategies, behavior modification strategies. Second, the application of general teacher strategies in learning Islamic religious education for deaf students consists of opening, core and closing activities. Third, the obstacles faced by general teachers in learning Islamic religious education for deaf students are in terms of internal factors, namely physiological factors, psychological factors, then finally, external factors including the social and non-social environment.